A new rescue regimen with plasma exchange and rituximab in high-risk membranous glomerulonephritis - Müller-Deile, Janina; Schiffer, Lena; Hiss, Marcus; Haller, Hermann; Schiffer, Mario (European Journal of Clinical Investigation, 2015)
BACKGROUND: Even though current treatment guidelines for idiopathic membranous glomerulonephritis (iMGN) exist, many questions regarding an optimal therapy remain unanswered. Complete remission cannot be achieved in all patients; relapses occur, in some cases frequently, and side effects from the immunosuppressive therapy are common. Therapeutic options in high-risk patients not responding to standard immunosuppressive therapies are limited. Recent research reveals that the human M-type phospholipase A2 receptor (PLA2 R) is a causative factor in iMGN that parallels clinical disease activity. However, in some patients, this correlation is not evident and additional undetermined factors seem to play a role. DESIGN: We evaluated a new rescue protocol including plasma exchanges (PE) against albumin, intravenous immunoglobulins (IVIGs) and rituximab for 10 patients with a biopsy-proven diagnosis of iMGN who were therapy-resistant to all conventional regimens and had a urinary protein to creatinine ratio of more than 10 000 mg/g Crea. We compared this protocol with standard immunosuppressive protocols including monthly alternating prednisolone plus cyclophosphamide (18 patients), cyclosporine plus prednisolone (23 patients) and rituximab alone (eight patients) in a retrospective design. RESULTS: Our rescue regimen with PE, IVIGs and rituximab achieved partial remission in 90% of patients who had been otherwise refractory to therapy. The mean time to partial remission was 2·1 months. Furthermore, two anti-PLA2 R-antibody negative patients were also treated with this rescue regimen, achieving partial remission after 1 and 4 months. CONCLUSION: A combination of PE, IVIGs and rituximab is a treatment option to consider for high-risk patients with iMGN who are refractory to conventional therapy.
EVALuna2:34561